KONSTITUSIONALITAS PEMBERHENTIAN SEMENTARA PEJABAT PUBLIK YANG DIDUGA ATAU DIDAKWA MELAKUKAN TINDAK PIDANA KORUPSI - Dinoroy Marganda Aritonang (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2019)
The problem of temporary dismissal of public officials frequently emerges along with the problem of corruption eradication. Some public officials who do not agree with the temporary dismissal procedures usually request a petition orjudicial review process to Constitutional Court (MK) related to laws regulating about his/her public position. The procedures of temporary dismissal for public officials are stipulated in one or more laws regulating the function and role ofa public institution where the public officials were used to work before. There are some terms and mechanisms within the related laws. But the point, the main reason why such public officials are dismissed temporarily from office is caused by a criminal accusation against the public official. Temporary dismissal left us with some very crucial questions, one of them is about the particular period of the dismissal that has to be obeyed by the public officials. The related law only provides an answer in a normative way. It is stated that the public official shall be released or appointed again when the court confirms that he/she is not guilty at all, then his/her power and name will be rehabilitated. This kind of uncertainty of the length on the dismissal period which is why usually considered to be a legal basis in order to propose a judicial review to MK, because the requester perceives that his/her loss can be categorized as aconstitutional loss. Besides, he/she would be thinking that the dismissal can be also considered as a violation to presumption of innocent principle. Another main problem is could it be right if the litigant considered that the temporary dismissal is a constitutional issue and then sending it to MK to be reviewed constitutionally. According to several MK's decision about these cases, MK has affirmed that the temporary dismissal is not a constitutional issue and can not be accepted as a constitutional loss. The exact place to argue that issue is DPR through legislative review. This research itself uses three type of approaches those are statute approach, comparative approach, and case approach.